Genetic diversity of the cave roosting dusky fruit bat, Penthetor lucasi from Sarawak - Mohd Ridwan, Abd Rahman; Manivannan, Yuvarajan; Roberta Chaya Tawie, Tingga; Faisal Ali, Anwarali Khan (Malaysian Society of Applied Biology, 2019)
Previous studies have revealed a high genetic divergence in Penthetor lucasi population in Sarawak, indicating it may consist of multiple genetic lineages. However, these studies are not accompanied by morphological data from the studied population suggesting this may be an effect of isolation by distance, especially with small sampling coverage. Here, we provide information based on D-loop sequence analysis from 32 individuals of Penthetor lucasi collected from four different regions in Sarawak. Our results revealed a high haplotype diversity and low nucleotide diversity, suggesting that these populations are possibly recovering from a recent geological and climatic event. However, neutrality test and mismatch distributions showed longterm population stability with no population subdivision observed among the studied populations. The moderate to high level of gene flow found in this study indicates that Penthetor lucasi population is likely panmictic. Meanwhile, the low level of genetic divergence value among and within populations could account for the absence of species complexity in this study. Our result highlighted the importance of sampling coverage in proper assessment of species diversity especially in species with wide distribution.